Value of IVIM in Differential Diagnoses between Benign and Malignant Solitary Lung Nodules and Masses: A Meta-analysis - Chen, Yirong; Han, Qijia; Huang, Zhiwei; Lyu, Mo; Ai, Zhu; Liang, Yuying; Yan, Haowen; Wang, Mengzhu; Xiang, Zhiming (Frontiers in Surgery, 2022)
Purpose: To evaluate the accuracy of intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) in distinguishing malignant and benign solitary pulmonary nodules and masses. Methods: Studies investigating the diagnostic accuracy of IVIM-DWI in lung lesions published through December 2020 were searched. The standardized mean difference (SMD) of apparent diffusion coefficient (ADC), tissue diffusivity (D), pseudo-diffusivity (D*), and perfusion fraction (f) were calculated. The sensitivity, specificity, area under curve (AUC), publication bias, and heterogeneity were then summarized, and the source of heterogeneity and the reliability of combined results were explored by meta-regression and sensitivity analysis. Results: A total of 16 studies including 714 malignant and 355 benign lesions were included. A significantly lower ADC, D, and f values were found in malignant pulmonary lesions compared to benign lesions. D value showed the best diagnostic performance (sensitivity = 0.90, specificity = 0.71, AUC = 0.91), followed by ADC (sensitivity = 0.84, specificity = 0.75, AUC = 0.88), f (sensitivity = 0.70, specificity = 0.62, AUC = 0.71), and D* (sensitivity = 0.67, specificity = 0.61, AUC = 0.67). There was inconspicuous publication bias in ADC, D, D* and f value, moderate heterogeneity in ADC but high heterogeneity in D, D* and f value. Subgroup analysis suggested that both ADC and D value had a significant higher sensitivity in “nodules or masses” than in “nodules”. Conclusions: The parameters derived from IVIM-DWI, especially the D value, could further improve the differential diagnosis between malignant and benign solitary pulmonary nodules and masses.